(untitled) (Journal of Fatima Jinnah Medical University, 2020)
Background: Dermatophytoses infections are widespread in the developing world. The laboratory diagnosis of dermatophytes has been a challenge as it involves microscopy and trained personnel. Potassium hydroxide wet mount with dimethyl sulfoxide added is routinely used in direct microscopy. But it lacks color contrast and the hyphae may be missed on routine microscopy. The study aimed to evaluate the effectiveness of the Chicago sky blue stain against routine potassium hydroxide-dimethyl sulfoxide (KOH/DMSO) wet mount in direct microscopy. Patients and methods: The study was carried out at the Department of Microbiology, Postgraduate Medical Institute, Lahore over a period of nine months from July 2013 till March 2014. Patients of either gender regardless of age, clinically diagnosed as having dermatophytoses by dermatologists were selected for this study. Specimens from 100 patients were collected from the dermatology outdoor of a tertiary care hospital for this study. They were evaluated microscopically with routine potassium hydroxide-dimethyl sulfoxide (KOH-DMSO) wet mount and Chicago sky blue (CSB) stain. Data were collected and entered in Statistical Package for the Social Sciences (SPSS) version 20.0. Results: Out of a total of 100 samples collected from skin, hair and nails, 59% were positive on direct microscopy with KOH/DMSO wet mount. Whereas direct microscopy using CSB stain revealed dermatophytes in 62% of cases. Conclusion: Chicago sky blue staining is a better technique for the detection of dermatophytes as compared to potassium hydroxide wet mount examination. It is simple, rapid, and easy to interpret. We recommend the use of this technique to improve the detection of dermatophytes without awaiting the results of the culture.